THE ROLE OF ECONOMIC INSTITUTIONS ACCORDING TO FAZLUR RAHMAN - Wan Ikhwanul Fazli (RUSYDIAH: Jurnal Pemikiran Islam, 2021)
Economic thoughts of Fazlur Rahman, a Pakistani modernist scholar and philosopher, have been discussed and studied frequently by many researchers. However, not much has been done to examine his thought of economic institutions holistically. This present study is aimed to analyse the role of the economic institutions according to Fazlur Rahman in the light of the Qur’ān and the Sunnah. This study is a library-based research, which uses two methods, namely data collection and data analysis. Rahman’s ideas on economic institutions are aimed to ensure the progressiveness of human beings while facing contemporary challenges through true understanding of the Qur’ān and the Sunnah. This study concludes that Rahman genuinely intended to develop Muslim societies through the re-evaluation of the Qur’ān and the Sunnah in the modern context